Sigma-term physics in the perturbative chiral quark model; Physical Review D; Vol. 63, iss. 5 - Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Gutsche Th.; Faessler A.; Drukarev E. G. (2001, 2001)
Title screen